2018
DOI: 10.1371/journal.pone.0199930
|View full text |Cite|
|
Sign up to set email alerts
|

Association of nefopam use with postoperative nausea and vomiting in gynecological patients receiving prophylactic ramosetron: A retrospective study

Abstract: BackgroundPostoperative nausea and vomiting (PONV) is a common adverse effect of opioid-based intravenous patient-controlled analgesia (IV PCA). Nefopam has been considered as a good candidate for inclusion in multimodal analgesia because of its opioid sparing effect, but it can be emetic. This study aims to examine whether the use of nefopam combined with fentanyl in IV PCA was associated with the higher incidence of PONV in patients receiving prophylactic ramosetron after gynecological surgery.MethodsData fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Opioids are known to induce PONV in 20–40% of patients [ 17 , 18 ], while nefopam is known to induce PONV in 15–30% of the patients [ 13 ]. In addition, according to the study by Oh et al [ 19 ], the PONV incidence was 31.9% in the group using nefopam and 57.4% in the group using fentanyl for post-gynecological pain control [ 19 ], but this study did not show a significant difference among the three groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Opioids are known to induce PONV in 20–40% of patients [ 17 , 18 ], while nefopam is known to induce PONV in 15–30% of the patients [ 13 ]. In addition, according to the study by Oh et al [ 19 ], the PONV incidence was 31.9% in the group using nefopam and 57.4% in the group using fentanyl for post-gynecological pain control [ 19 ], but this study did not show a significant difference among the three groups.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, an NRS pain score difference of 1 was considered as the non-inferiority margin. Based on a previous study [ 13 ], a standard deviation of 1.6 was assumed for the NRS distribution of laparoscopic gynecological surgery. To achieve a power of 80% with a risk of 0.025 for type 1 errors, the minimum number of patients required in each group was 41.…”
Section: Methodsmentioning
confidence: 99%
“…Although previous reports compared the analgesic or adverse effect between nefopam and opioids, each study showed an incoherency in their methods, particularly in the study population, anesthetic setting, the type of surgery, etc. [23].…”
Section: Discussionmentioning
confidence: 99%
“…Although opioids remain a cornerstone for postoperative pain management [ 1 , 3 , 5 , 6 ], opioid use is associated with undesirable effects including postoperative nausea and vomiting (PONV) [ 4 , 6 , 7 , 8 , 9 , 10 ]. In particular, gynecological surgery is associated with an increased risk of PONV, of which the incidence was reported in 26–57% of women [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%